Pengaruh Penggunaan Media Pembelajaran Berbasis Audio Visual terhadap Kemampuan Pembendaharaan Kosakata pada Anak Usia 4–5 Tahun di TK H. Dermawan Harahap Gonting Julu Huristak Padang Lawas - Daulay, Mastianur; Hasibuan, Humaidah (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of vocabulary acquisition in early childhood as a foundation for language development, as well as the need for engaging and effective learning approaches. The research aims to examine the vocabulary development of children aged 4–5 years through audio-visual media-based learning and to measure its effect on their vocabulary mastery at TK H. Dermawan Harahap, Gonting Julu, Padang Lawas Regency. The method used is an experimental design with a One Group Pretest–Posttest design within a quantitative approach. The subjects were 4–5-year-old children who had not previously received instruction using audio-visual media. Data were collected through pre-test and post-test assessments designed to measure vocabulary ability before and after the intervention. The results show that the average pre-test score of 66.5% increased to 82% in the post-test, indicating a significant improvement. The Paired Samples Test yielded a significance value of p = 0.000, demonstrating that the use of audio-visual media has a significant effect on enhancing children's vocabulary skills. The study concludes that learning through audio-visual media is effective in enriching early childhood vocabulary, as the media combine visual and auditory elements that capture attention and facilitate children's understanding of new vocabulary.